COVID-19 Pandemic’s Effects on Breast Cancer Screening, Staging at Diagnosis at Presentation, Oncologic Management, and Immediate Reconstruction: A Canadian Perspective - Adolfo Alejandro Lopez Rios; Alissa Dozois; Alexander T. Johnson; Toros Canturk; Jing Zhang (Current Oncology)
Background: Did the COVID-19 pandemic lead to delays in breast cancer management, impacting treatment recommendations? The goal of this study was to assess the pandemic’s effect on breast cancer treatment and management practices. Methods: This study aimed to assess the pandemic’s effect on breast cancer treatment from March 2018 to February 2020 (pre-pandemic) and March 2020 to February 2022 (during the pandemic) in Canada. A retrospective cohort study at The Ottawa Hospital, Ontario, Canada, compared breast cancer patients diagnosed in the two years before and after the pandemic’s onset. The study examined patient demographics, cancer stages, treatment timelines, and procedures, including neoadjuvant chemotherapy, endocrine therapy, and surgical treatment. Descriptive statistics and frequencies identified changes. The study is limited to a single institution, which may restrict generalizability. Inclusion criteria focused on female patients over 18 years with newly diagnosed breast cancer, excluding recurrent cases. Stage IV patients were included, but further details on their management are needed. Results: Breast cancer diagnoses decreased from 2577 before the pandemic to 2290 after its onset. Surgeries decreased from 1226 to 1013 (p < 0.020), while neoadjuvant endocrine therapy increased from 148 to 169, and adjuvant radiotherapy rose from 586 to 722 (p < 0.001). The study revealed a decrease in breast cancer diagnoses and surgeries during the pandemic, with a rise in non-surgical treatments. Conclusions: These changes indicate significant shifts in breast cancer management due to the pandemic. The decrease in surgical treatments and increase in non-surgical options such as endocrine therapy and radiotherapy suggest adaptations in clinical practices to cope with the challenges posed by the pandemic. Understanding these shifts is crucial for developing strategies to mitigate the impact of future disruptions on breast cancer care and ensuring optimal patient outcomes.